Determining Morphological Traits for Selecting Wheat (Triticum Aestivum L.) with Improved Early-Season Forage Production - Malinowski, Dariusz P; Rudd, Jackie C; Pinchak, William E; Baker, Jason A (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Winter wheat (Triticum aestivum L.) is the major annual crop in the Southern Great Plains of the USA grown as dual-purpose (forage and grain) crop. Wheat breeding has focused on maximizing grain yield and tolerance to abiotic and biotic stresses. Because of a lack of clearly defined selection criteria for breeding forage-type wheat, breeders usually rely on very laborious means to measure forage quantity and quality or they use imprecise visual estimates to quantify forage production. In a series of experiments conducted at Vernon, TX during 2003-2005, we determined correlations between selected morphological traits and the early-season forage DM yield in a range of wheat breeding lines and commercial cultivars evaluated by the Wheat Breeding Program of Texas A&M AgriLife Research. Early-season forage DM yield was highly correlated with tiller number, leaf length and width, and inversely correlated with specific leaf weight. Environmental variables modified the responses. A number of wheat breeding lines and cultivars had combined three out of the four evaluated morphological traits, including Abilene Ag Exp., Cutter, Fannin, HG-9, Duster, TAM 110, TX01M5009, TX01V6016, TX03M1179, TX04M410009, and Weather master 135. These cultivars/breeding lines have been recommended for dual-purpose use; thus, the morphological traits evaluated in our studies were desirable for selection of wheat with improved forage productivity.